PEMBERDAYAAN SISWA MALAS, NAKAL, RUNDUNG MELALUI KATARSIS MENULIS ASYIK REFLEKTIF - Alamsyah, Muh. Nur; Alfiyah, Faridah; Anugerah, Muh. Fahmi; Nabilah, Naimah Zhahratun; Sultan, Sultan (Jurnal Graha Pengabdian, 2024)
MTs Muhammadiyah Julubori is a private school located in the middle of the village ofJulukanaya and has access to a remote city center. Based on the data obtained, currentlystudents who have the category of lazy, naughty, bullied out of a total of 129 students areseen from the attendance of class VII A 5 people, VII B 3 people, IX A 2 people, VIII B 2people, and IX B 3 people. From these data, each student has a different motive. Oneapproach to make students aware of lazy, naughty, bullied, through catharsis, writing, fun,reflective. The aims of the reflective writing catharsis are as follows: As an effort topsychologically approach students who experience deviations in the school environment,findstepstoempowerlazy,naughty,bulliedstudents,whichcanbeareferenceforhandlingproblematic students, MTs. Muhammadiyah Julubori is carried out through five stages,namely:(1)Preparation,(2)Interventionforhandlingpartnerproblems,(3) Writingassistance with catharsis, writing, fun, reflective (4) Implementation of the results of theinterventionandwritingassistance,(5)Evaluationandfinalreport.ThisprogramiscarriedouttopresenttheconceptoftheEmpowermentprogramforlazy,naughty,bulliedstudentsthroughwriting,fun,reflectivecatharsiswhoexperiencedeviationsatschool.Throughthework of students, it is expected to be able to become a reflection material for students tofeelcalmandmoreopenthroughwritingbyusingwritingcatharsis,fun,reflective.Writingis expected to be able to produce written works in the form of books as a form of studentempowermentthatcanbereadbythecommunity.Studentwritingcaninspiremanypeople,especially for students at school. And the school can find a pattern of handling that is areferenceforteachers.